Spectrophotometric Analysis of Hydrochlorothiazide Tablets using Chlorpheniramine Maleate as Hydrotropic Solubilizing Agent - Maheshwari, R.K.; Bishnoi, S.R.; Kumar, D. (Asian Journal of Chemistry, 2010)
In present work, hydrotropic solution of chlorpheniramine maleate (20 % w/v) was employed to solubilize hydrochlorothiazide (a poorly water-soluble drug) from fine powder of its tablets, to carry out spectrophotometric analysis at 317 nm. Beer's law was obeyed in the concentration range of 30-180 mcg/mL. Recovery studies and statistical data proved the accuracy, reproducibility and the precision of the proposed method. Presence of chlorpheniramine maleate and commonly used tablet excipients did not interfere in the analysis.